1988
DOI: 10.1056/nejm198806093182302
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Glucose Concentrations at the Onset of Hypoglycemic Symptoms in Patients with Poorly Controlled Diabetes and in Nondiabetics

Abstract: We tested the hypothesis that during decrements in plasma glucose concentration, symptoms of hypoglycemia may occur at higher glucose concentrations in patients with poorly controlled insulin-dependent diabetes mellitus than in persons without diabetes. Symptoms of hypoglycemia and counterregulatory neuroendocrine responses were quantified during hypoglycemic and euglycemic clamp studies in eight patients with insulin-dependent diabetes mellitus selected because their hemoglobin A1 levels were above 10 percent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
126
3
3

Year Published

1992
1992
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(137 citation statements)
references
References 28 publications
5
126
3
3
Order By: Relevance
“…Elevation of plasma insulin to a mean steadystate level of 46 mU/1 [22] or 100-200 mU/1 failed to elevate plasma catecholamines [23,24], whereas other investigations have found minor but significant elevations of plasma noradrenaline at plasma insulin concentrations ranging from a level corresponding to postprandial hyperinsulinaemia in normal and insulin-resistant subjects, i. e. less than 100 mU/1 [25] to supraphysiological levels [6,7,26]. The occasional failure to observe increases in plasma noradrenaline may be methodological, as moderate hyperinsulinaemia is apparently a weak sympathetic stimulus.…”
Section: Discussionmentioning
confidence: 97%
“…Elevation of plasma insulin to a mean steadystate level of 46 mU/1 [22] or 100-200 mU/1 failed to elevate plasma catecholamines [23,24], whereas other investigations have found minor but significant elevations of plasma noradrenaline at plasma insulin concentrations ranging from a level corresponding to postprandial hyperinsulinaemia in normal and insulin-resistant subjects, i. e. less than 100 mU/1 [25] to supraphysiological levels [6,7,26]. The occasional failure to observe increases in plasma noradrenaline may be methodological, as moderate hyperinsulinaemia is apparently a weak sympathetic stimulus.…”
Section: Discussionmentioning
confidence: 97%
“…Whereas the glycaemic thresholds for these responses (mean arterialised venous plasma glucose concentrations of about 4.5 mmol/l (81 mg/dl), 3.7 mmol/l (67 mg/dl) and 3.0 mmol/l (54 mg/dl) respectively) are reproducible in healthy subjects [13,14,15], they shift to higher plasma glucose concentrations in poorly controlled diabetes [16,17] and to lower plasma glucose concentrations following episodes of hypoglycaemia [18,19,20,21]. These threshold shifts are of considerable relevance to the pathogenesis of iatrogenic hypoglycaemia in diabetes.…”
Section: Pathophysiology Of Glucose Counterregulation In Type I Diabetesmentioning
confidence: 97%
“…An event during which the person with diabetes reports any of the typical symptoms of hypoglycemia, and interprets those as indicative of hypoglycemia, but with a measured plasma glucose concentration Ͼ70 mg/dl (3.9 mmol/l). This category reflects the fact that patients with chronically poor glycemic control can experience symptoms of hypoglycemia at plasma glucose levels Ͼ70 mg/dl (3.9 mmol/l) as plasma glucose concentrations decline toward that level (27,28). Though causing distress and interfering with the patient's sense of well-being, and potentially limiting the achievement of optimal glycemic control, such episodes probably pose no direct harm and therefore may not be a suitable outcome measure for clinical studies that are aimed at evaluating therapy, but they should be reported.…”
Section: A) How Should Hypoglycemia Be Defined?mentioning
confidence: 99%